Search for the Standard Model Higgs boson in the two photon decay channel with the ATLAS detector at the LHC - Anduaga, Xabier Sebastián (2011)
A search for the Standard Model Higgs boson in the two photon decay channel is reported, using 1.08 fb-1 of proton–proton collision data at a centre-of-mass energy of 7 TeV recorded by the ATLAS detector. No significant excess is observed in the investigated mass range of 110–150 GeV. Upper limits on the cross-section times branching ratio of between 2.0 and 5.8 times the Standard Model prediction are derived for this mass range.